Remembering the Civil War : Reunion and the Limits of Reconciliation - Janney, Caroline E. (Book collections on Project MUSE., 2013)
As early as 1865, survivors of the Civil War were acutely aware that people were purposefully shaping what would be remembered about the war and what would be omitted from the historical record. In Remembering the Civil War, Caroline E. Janney examines how the war generation--men and women, black and white, Unionists and Confederates--crafted and protected their memories of the nation's greatest conflict. Janney maintains that the participants never fully embraced the reconciliation so famously represented in handshakes across stone walls. Instead, both Union and Confederate veterans, a.